2023
DOI: 10.1093/bjd/ljad148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of house dust mite in vitiligo skin: environmental contribution to increased cutaneous immunity and melanocyte detachment

Abstract: Background Vitiligo is an autoimmune skin disorder characterized by loss of melanocytes. Protease-mediated disruption of junctions between keratinocytes and/or keratinocyte intrinsic dysfunction may directly contribute to melanocyte loss. House dust mite (HDM), an environmental allergen with potent protease activity, contributes to respiratory and gut disease but also to atopic dermatitis and rosacea. Objective To verify if H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…SE-Cad and SN-Cad have different functions compared to the full-length Cadherin. Nevertheless, in different cells types and tissues such as in endothelial cells, keratinocytes, pulmonary fibrosis, tumor, and inflammatory diseases, both SE-Cad and SN-Cad demonstrate a promoting effect on cell migration [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…SE-Cad and SN-Cad have different functions compared to the full-length Cadherin. Nevertheless, in different cells types and tissues such as in endothelial cells, keratinocytes, pulmonary fibrosis, tumor, and inflammatory diseases, both SE-Cad and SN-Cad demonstrate a promoting effect on cell migration [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…This was associated with increased in situ MMP-9 activity, reduced cutaneous expression of adherent protein Ecadherin, increased soluble E-cadherin in culture supernatant and significantly increased number of supra-basal melanocytes in the skin. This effect was dose-dependent and driven by HDM-containing cysteine protease Der p1 and MMP-9 [18].…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, in addition to allergenic properties, there is evidence to suggest that the potent protease activity of mites can disrupt the skin epithelial barrier, promoting trans-epidermal water loss and facilitating the penetration of allergens directly into the skin [17]. We have recently shown that in human skin, HDM increased keratinocyte production of vitiligo-associated cytokines and chemokines [18]. This was associated with increased in situ MMP-9 activity, reduced cutaneous expression of adherent protein Ecadherin, increased soluble E-cadherin in culture supernatant and significantly increased number of supra-basal melanocytes in the skin.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evidence suggests that house dust mites might contribute to the pathogenesis of intestinal destruction by compromising tight junctions between group 1 major allergens with cysteine protease activity and epithelial cells [ 19 ]. Apart from their significant impact on respiratory and gastrointestinal ailments, mites are recognized culprits in the development of atopic dermatitis, acne, and rosacea in human skin [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%